The psychological impact of conflict in the Middle East from 2023 to 2025 on Australian communities: a prospective cohort studyResearch in context - Susan J. Rees; Tyson Whitten; Alvin Kuowei Tay; Aino Suomi; Batool Moussa; Fatima Hassoun; Nawal Nadar; Derrick Silove (The Lancet Regional Health. Western Pacific, 2025)
Summary: Background: There is a lack of empirical research on the mental health risks faced by populations living in high-income multicultural countries during a war in their country of origin. We examined mental health and psychosocial outcomes associated with a period during the 2023–2025 Middle East conflict (primarily involving Israel, Palestine and Lebanon) on Australian resident women including those who arrived from Lebanon, Gaza and other Palestinian Territories. Methods: The mental health study assessed 410 Australian resident women at two points: one 12–18 months prior, and one period during the current Middle Eastern conflict extending from October 7, 2023, to December 2024. The three groups included those directly connected by birth or family to the conflict-affected regions: Lebanon, Gaza and other Palestinian territories (Middle East—LGP), Other Migrants not from the region, and Australian Born (AB) women with no connection to the region. Measures included the Mini-International Neuropsychiatric Interview to assess symptoms of panic disorder (PD), mood disorder (MDD), post-traumatic stress disorder (PTSD), separation anxiety disorder (SEPAD), Quality of Life, Worry about Family and Separation from Family overseas. Generalised linear mixed models and cumulative link mixed models were used to examine the trajectory of mental disorder symptoms over time for each group compared with the AB group. The analysis adjusted for age, marital status, financial difficulties, and COVID-19 stress. Findings: Generalised linear and cumulative link mixed models revealed significant interaction effects, indicating that Middle East–LGP women experienced a significantly greater increase in PD symptoms (β = 1.26, SE = 0.54, p = 0.02) and poorer quality of life (β = 0.10, SE = 0.04, p = 0.009) from Time 1 to Time 2 compared to AB women. The Middle East—LGP women reported significantly greater increases in concerns about family overseas (log odds = 4.04, SE = 1.25, p = 0.001) and the ability to return home in an emergency (log odds = 3.41, SE = 1.20, p = 0.005). Interpretation: This is a unique study of women’s mental health in a multicultural, high-income country, undertaken during conflict occurring in another region of the world. Panic Disorder symptoms, poorer quality of life and other psychosocial stress increased only in the group connected by migration to the conflict-affected region. Funding: National Health and Medical Research Council, Australia (2018/GNT1164736).